The quality of housing produced by the low income in a developing country : a case study in Ibadan, Nigeria / Jaiyeoba Babatunde Emmanuel - Emmanuel, Jaiyeoba Babatunde (Faculty of Architecture, Planning and Surveying, 2013)
The paper illustrates how housing produced by the low income in Ogbere area of Ibadan is negotiated from the societal complex due to the inability of government to provide for them and low income housing not being attractive to the profit driven private sector. Quantitative and qualitative methods were adopted while using the lens of Lefebvre’s theory of space to examine the people, the process and the houses produced. The findings necessitate situating low income housing standards, quality and policy interventions in the social context to upgrade the quality of life in urban areas.